Approaches for Producing Fungal Cellulases Through Submerged Fermentation - Madiha Nazir; Attia Iram; Deniz Cekmecelioglu; Ali Demirci (Frontiers in Bioscience-Elite, 2024)
Fungal cellulases are the most sought-after biological molecules produced from microbial sources in the last four decades. Owing to their emerging applications in the bioenergy industry for hydrolyzing cellulose, for which they are the most abundant source on this planet, research trends are shifting heavily toward adapting to submerged fermentation. However, filamentous fungal species, which are efficient cellulase producers, are well-adapted to low-moisture solid support as the substrate, such as in nature. Therefore, various fermentation strategies are currently being investigated to adapt them to submerged fermentation for large and high-quality production of cellulases. Emerging research trends, such as the use of inexpensive feedstocks, nutrient and/or culture optimization, innovative bioreactor designs, microparticle-assisted fungal growth, and innovative genetic engineering approaches, are some of the recent efforts by researchers to exploit the full potential of these biological molecules. This review discusses some of these strategies and their success rates in various research conditions. In addition, specific focus was provided to both increasing the market value of cellulases and the innovative strategies required to enhance their production on an industrial scale.